2020
DOI: 10.1186/s40104-020-00471-0
|View full text |Cite
|
Sign up to set email alerts
|

Sow performance in response to natural betaine fed during lactation and post-weaning during summer and non-summer months

Abstract: Background: Two studies were conducted to evaluate the effects of dietary natural betaine on sow reproductive performance during summer (Exp. 1) and non-summer months (Exp. 2). Treatments were designed as a 2 × 2 factorial arrangement with factors including dietary betaine (0 or 0.2%) and period of supplementation (lactation or post-weaning until 35 days post-insemination). In Exp. 1, 322 and 327 sows and in Exp. 2, 300 and 327 sows representing young (parity 1 and 2) and mature (parity 3 to 6) sows, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…This conclusion was supported by Huang et al. (2008) and Mendoza et al (2010) in pigs who also found that betaine supplementation could promote lipid metabolism. The result was consistent with the known lipid-reducing effects of betaine.…”
Section: Discussionmentioning
confidence: 70%
“…This conclusion was supported by Huang et al. (2008) and Mendoza et al (2010) in pigs who also found that betaine supplementation could promote lipid metabolism. The result was consistent with the known lipid-reducing effects of betaine.…”
Section: Discussionmentioning
confidence: 70%
“…18 Studies have shown that dietary supplementation with 200 mg kg −1 betaine during lactation and post-weaning did not affect the sow performance during the non-summer months, whereas it increased the litter size during the summer months. 26 Furthermore, supplementing 1000 or 2000 mg kg −1 betaine to pregnant sows under heat stress tended to increase the litter size. 27 Therefore, inconsistent production performance might be related to the environmental or biological functions of betaine, such as inducing feed intake, maintaining osmotic pressure, and anti-stress.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that dietary betaine addition in sow diets at 3.50 kg ton −1 during gestation and lactation reduced the mortality rate and increased the number of weaned piglets, indicating that betaine could improve the production performance of sows to a certain content 18 . Studies have shown that dietary supplementation with 200 mg kg −1 betaine during lactation and post‐weaning did not affect the sow performance during the non‐summer months, whereas it increased the litter size during the summer months 26 . Furthermore, supplementing 1000 or 2000 mg kg −1 betaine to pregnant sows under heat stress tended to increase the litter size 27 .…”
Section: Discussionmentioning
confidence: 99%
“…La respuesta en el consumo de los animales no puede atribuirse al componente betaína en el producto comercial, ya que en la literatura se han reportado respuestas variables, por ejemplo, Mendoza et al (2020) y Ramis et al (2011) reportaron una disminución del consumo al usar 0,20 % de betaína durante los meses de verano, mientras que Cabezón et al (2016), indicaron que el uso de betaína mejoró el consumo de cerdas en lactancia durante el verano.…”
Section: Variableunclassified
“…La suplementación de betaína en un 0,20 % en cerdas en lactancia, produjo camadas 12 % más pesadas que el tratamiento control (Ramis et al, 2011), lo cual difiere de los resultados del presente estudio. En otro estudio no se reportaron diferencias en los parámetros zootécnicos de la camada (Mendoza et al, 2020;Sureshkumar et al, 2021). Las ganancias de peso en el actual experimento estuvieron por debajo de los 200 g/día, por una posible producción baja de leche por parte de la cerda, debido al bajo consumo de alimento (Cuadro 3).…”
Section: Variableunclassified